Fonds Régional d'Art Contemporain - Limousin 1989-1995 : "deuxième époque". - Armstrong, Richard; Besson, Christian; Bourzai, Bernadette; Paul, Frédéric; Savy, Robert; Semin, Didier; Soulillou, Jacques; Tió Bellido, Ramon; Vulliez, Roger; de Canchy, Jean-François (Limoges : Fonds Régional d'Art Contemporain - Limousin, 1996)
Aballéa, Martine ; Acconci, Vito ; Adams, Mac ; Ader, Bas Jan ; Armleder, John M ; Aubry, Michel ; Bartoloméo, Joël ; Bossut, Etienne ; Bouillon, François ; Burden, Chris ; Calle, Sophie ; Closky, Claude ; Cohen, Lynne ; Colomer, Jordi ; Corillon, Patrick ; Culbert, Bill ; Cumming, Robert ; Currin, John ; Dimitrijevic, Braco ; Duprat, Hubert ; Fauguet, Richard ; François, Michel ; Fridfinnsson, Hreinn ; Grand, Toni ; Grigely, Joseph ; Hamilton, Richard ; Huebler, Douglas ; Hutchinson, Peter ; Journiac, Michel ; Lüthi, Urs ; Mariën, Marcel ; Matta-Clark, Gordon ; Mogarra, Joachim ; Monnier, Richard ; Muñoz, Juan ; Opie, Julian ; Paradeis, Florence ; Pippin, Steven ; Pouvreau, Paul ; Rabascall, Joan ; Raetz, Markus ; Righi, François ; Rullier, Jean-Jacques ; Ruppersberg, Allen ; Schütte, Thomas ; Séchas, Alain ; Valensi, André ; Van Caeckenbergh, Patrick ; Vieille, Jacques ; Vulliez, Roger ; Webb, Boyd ; Wegman, William ; Whiteread, Rachel
biografie
Frans
boek